2009
DOI: 10.1517/14712590903066711
|View full text |Cite
|
Sign up to set email alerts
|

Serological response to tick-borne encephalitis (TBE) vaccination in the elderly – results from an observational study

Abstract: After two doses of TBE vaccine, one in five persons aged 60 years or older may be without protective antibodies, confirming the importance of testing the antibody response after the second vaccination and administering an additional dose in the event of insufficient response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Since all our study participants from the Åland Islands had been vaccinated with the FSME-IMMUN vaccine, we could not investigate if there was any difference in sensitivity and specificity with regard to the Enzygnost and Immunozym assay as an effect of homologous or heterogeneous TBEV strains in the vaccine and ELISA assays, as reported by Jílková et al [28]. The discrepancy between the Immunozym assay compared to the Enzygnost and RFFIT assay is fully accounted for by the difference in cut-off levels chosen as shown by the ROC curve analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since all our study participants from the Åland Islands had been vaccinated with the FSME-IMMUN vaccine, we could not investigate if there was any difference in sensitivity and specificity with regard to the Enzygnost and Immunozym assay as an effect of homologous or heterogeneous TBEV strains in the vaccine and ELISA assays, as reported by Jílková et al [28]. The discrepancy between the Immunozym assay compared to the Enzygnost and RFFIT assay is fully accounted for by the difference in cut-off levels chosen as shown by the ROC curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The Novartis Encepur vaccine on the other hand, uses the K23 TBEV strain, as does the Enzygnost ELISA assay. A study by Jílková et al [28] found that the results differed significantly between the two ELISA assays depending on whether the TBEV strain was heterologous or homologous with respect to the vaccine used. Neutralizing antibody tests do not suffer from this potential bias and are considered to be the best surrogate marker of protection against TBEV [27], [29].…”
Section: Introductionmentioning
confidence: 99%
“…The K23 and Neudoerfl strains are used in the European vaccines Encepur (Novartis Vaccines and Diagnostics GmbH & Co., Marburg, Germany) and FSME-Immun (Baxter AG, Vienna, Austria), respectively. Both vaccines induce neutralizing antibodies against all three subtypes of TBEV, but there might be some differences in reactivity depending on whether homologous or heterologous coating antigens were used for the vaccine (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Jilkova et al recently found that 18% of individuals aged 60 years or above had antibody concentrations below putative protective levels after 2 of the first 3 vaccinations required for primary immunization [27]. A study on TBE booster vaccination reporting 6-year follow-up data showed that antibody levels were 2 times lower in vaccinees 60 years of age or older, implying some waning of antibodies with increasing age [28].…”
Section: Tbe and The Ageing Immune Systemmentioning
confidence: 99%